التعريف بكتاب الكلّيّات لأبي البقاء الكفويّ (ت1094ه) - ياسين مالك; جمعة ميساء (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يتناول هذا البحث كتاباً اصطلاحياً عاماً قلما تعرّض له الباحثون بالدرس والتحليل, وهو كتاب الكليات لأبي البقاء الكفوي (ت1094ﻫ)؛ في محاولةٍ لتقديم وصفٍ شاملٍ لمنهجية المؤلف فيه, فيترجم لأبي البقاء بداية, ويحاول معرفة الغرض من تأليفه هذا الكتاب, ثم يدرس مصادره, ومادته, وطريقة ترتيب هذه المادة وشرحها، بالإضافة إلى أهمّ المزايا التي يمتاز بها هذا المصنف عن غيره من الكتب الاصطلاحية. ويختم البحث بخاتمةٍ توجز أهمّ النتائج والتوصيات التي تمّ التوصّل إليها. This research deals with a general professional book which is rarely studied nor analyzed by researchers.It´s AL Koulliat by Abi ALbakáa ALkafawi. It tries tointroduce a comprehensive description of this book.In the beginning, the research speaks about the biography of his writer and tries to know the purpose of its writing, examine its sources and subject, and how to classify and explainit.In addition, the research examines the most important characteristics of the book which is distinguished from other idiomatic books. The research sumsup the most important results and commandments.